ÅPara qué las TIC? : estudio sobre el proceso de diseño educativo desde una perspectiva sociocultural (2017)
This study explores how ICTs could enhance teaching and learning processes and how such improvement is constituted during the educational design. In contrast to studies that explore the use of ICT in the classroom, the present research set out to observe an educational design process, its pilot test in the classroom and the adjustments made after said pilot. The main results show, firstly, that ICT was a catalyst in the transformation of the educational process by way of changing the joint activity between teacher and student. Secondly, three dimensions were discovered in order to analyze the role of ICT in educational design: i) that which is specifically permitted by the use of technology, ii) the changes generated by these specific uses of ICT in the individual teacher / student activity and iii) the kind of joint activity which is made possible due to the independent actions before mentioned...